Wound Dehiscence Pasca-Laparatomi: Sebuah Laporan Kasus - Ahsan Ahsan; Mohammad Arifin; Peter Ian Limas (Jurnal Impresi Indonesia, 2025)
Wound dehiscence is a serious postoperative complication characterized by the reopening of the surgical incision wound and is reported to occur in about 0.5–3.4% of abdominopelvic surgery cases. These complications generally appear on the 5th to 8th day postoperatively, especially in the proliferation phase of the wound healing process. Various risk factors play a role in the occurrence of wound dehiscence, including surgical wound infection, poor nutritional status, anemia, and comorbid diseases such as uncontrolled diabetes mellitus. The case report discusses a 46-year-old male patient with a history of uncontrolled diabetes mellitus who experienced wound dehiscence after undergoing an exploratory laparotomy. Patients complain of detached wound sutures accompanied by pain and signs of local infection. Clinical and laboratory examinations show the presence of leukocytosis, anemia, and hypoalbuminemia that worsen the wound healing process. Management is carried out through reoperation to close the wound and give broad-spectrum antibiotics to control infection. The results of the treatment showed a gradual improvement in the patient's clinical condition. This case confirms the importance of early detection of risk factors, control of comorbidities, and appropriate surgical and medical treatment in preventing advanced complications such as evisceration and sepsis. A comprehensive approach is indispensable to improve the outcomes of patients with postoperative wound dehiscence.